Salinomycin poisoning in cattle Intoxicação por salinomicina em bovinos - Gava A.* (1997)
An outbreak of salinomycin toxicosis is reported. Out of a lot of 46 Simmental heifers 13 died after presenting incoordination, stiff gait, diarrhea, weight loss, muscle tremors, reduced tolerance to exercise, dyspnea and, occasionally, dark urine. Some animals were found dead or died when forced to move. Gross lesions consisted basically of pale areas in the myocardium, subepicardial hemorrhages, hydropericardium, hydrothorax, pulmonary congestion and edema, and, in some cases, pendent subcutaneous edema and nutmeg liver. Main histopathological changes consisted of necrosis and loss of myocardial fibers which were replaced by fibrous connective tissue. Approximately 9 days before the first deaths the heifers had been treated for eimeriosis with a premix containing 6% of salinomycin.